Chromosomal Abnormalities and Pregnancy Outcomes for Fetuses With Gastrointestinal Tract Obstructions - Wu, Xiaoqing; Su, Linjuan; Shen, Qingmei; Guo, Qun; Li, Ying; Xu, Shiyi; Lin, Na; Huang, Hailong; Xu, Liangpu (Frontiers in Pediatrics, 2022)
This study investigated the genetic disorders as well as pregnancy outcomes of fetal gastrointestinal tract obstructions (GITO). We reviewed data from 70 pregnancies who were referred for invasive prenatal testing due to fetal GITO between May 2012 and November 2021. According to the levels of obstruction, they were classified into esophageal atresia/stenosis, duodenal atresia/stenosis, jejunal and ileal atresia/stenosis, or anal atresia. Traditional karyotyping was performed on all 70 pregnancies, and SNP array analysis was performed on 32 of them in parallel. Traditional karyotyping revealed twelve (17.1%) chromosomal abnormalities, including 11 cases of trisomy 21 (Down syndrome), and one case of a supernumerary marker chromosome related to Cat Eye Syndrome. According to the absence or presence of other ultrasound anomalies, they were categorized into isolated GITO (n = 36) and non-isolated GITO (n = 34). The rate of chromosomal abnormalities in non-isolated GITO pregnancies was significantly higher than that in isolated GITO pregnancies (29.4% vs. 5.5%, p < 0.05); the survival rate in isolated group was significantly higher than that in non-isolated group (67.6% vs. 34.4%, p<0.05). Among the 32 cases where CMA was performed, additional one (3.1%) copy number variants with clinical significance was noted in a fetus with normal karyotype. The microduplication on 7q12 was consider to be the genetic etiologies of duodenal stenosis, although it was inherited from a phenotypically normal mother. Our study supports the strong association between Down syndrome and fetal GITO, especially duodenal stenosis. Our findings suggested that the risk of chromosomal abnormalities increased when GITO was accompanied by other ultrasound anomalies, thus chromosomal abnormalities and fetal anatomy should be carefully evaluated for pregnancy management of fetal GITO.